Magnetohydrodynamics (MHD) boundary layer flow of hybrid nanofluid over a moving plate with Joule heating - Khashi'ie, Najiyah Safwa; Md Arifin, Norihan; Pop, Ioan (Elsevier, 2022)
The proficiency of hybrid nanoparticles in augmenting the heat transfer has fascinated many researchers to further analysing the working fluid. The present paper is focused on the MHD hybrid nanofluid flow with heat transfer on a moving plate with Joule heating. The combination of metal (Cu) and metal oxide (Al2O3) nanoparticles with water (H2O) as the base fluid is used for the analysis. Similarity transformation reduces the complexity of the PDEs into a system of ODEs, which is then solved numerically using the function bvp4c from MATLAB for different values of the governing parameters. Two solutions are obtained when the plate is moved oppositely from the free stream flow. Analysis of flow stability unveils the first solution as the real physical solution, which is realizable in practice. From physical perspective, the real solution must be available for all cases of λ which affirms the finding from stability analysis. An upsurge of suction’s strength and magnetic parameter enhances the heat transfer operation and extends the critical value λc. Meanwhile, there is no change on the critical value when the Eckert number is added. This study is important in determining the thermal behavior of Cu-Al2O3/H2O when the physical parameters like magnetic field and Joule heating are embedded. The results are new and original with many practical applications in the modern industry.